Lightweight high-strength Ni-Co-based single-crystal high-entropy alloy and preparation method thereof
By designing Ni-Co-based single crystal high-entropy alloy, combining thermodynamic calculations and fine process flow, the problems of unbalanced performance and high density of single crystal high-entropy alloys are solved, and lightweight, high strength and excellent mechanical properties are achieved. for high temperature applications.
Patent Information
- Application Number
- CN202411307685.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The existing single crystal high-entropy alloys have unbalanced performance at room temperature and high temperature, and it is difficult to achieve both strength and plasticity. In addition, traditional alloys have high density, making it difficult to meet the needs of lightweight and high strength.
Design Ni-Co-based single crystal high-entropy alloy with chemical components including Ni, Co, Cr, Al, Ti, Mo, W, Hf. It is prepared by thermodynamic calculation simulation and fine process flow, using high-speed solidification and seed crystal method to perform Solid solution treatment and aging treatment optimize grain orientation and tissue structure to form low-density and high-strength alloys.
It achieves a balance between room temperature and high temperature mechanical properties, significantly improves tensile strength and elongation, reduces density, and does not contain rare and precious elements. It has operational and cost advantages, and is suitable for high-temperature applications.
Smart Images

Figure CN119194200A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of single crystal high entropy alloy materials and preparation thereof, and in particular relates to a lightweight and high-strength Ni-Co based single crystal high entropy alloy and a preparation method thereof. Background Art
[0002] As we all know, high entropy alloy refers to a new alloy system with four or more components, and the atomic ratio of each component is equal or nearly equal. A lot of research has been carried out on high entropy alloys in aspects such as directional solidification. Its composition design has unlimited potential and can meet the needs of single-crystal turbine blades for light weight, high strength and high temperature resistance. Traditional single-crystal high-temperature alloys are alloys with Fe, Co, Ni and other elements as the main matrix elements. By adding more than ten strengthening elements, they have super high-temperature mechanical properties and creep resistance after eliminating the influence of grain boundaries, but their development has reached a bottleneck. On the basis of single-crystal high-temperature alloys, new single-crystal high-entropy alloys can be defined as alloys composed of four or more elements, conforming to the characteristics of single-crystal structure, and satisfying thermodynamic, kinetic and other conditions during the single-crystal formation process, and the mixing entropy is greater than 1.38R.
[0003] There are two development directions for single crystal high entropy alloys in existing technology: one is the single crystalization of high entropy alloys, such as CoCrFeMnNi, AlCoCrFeNi or transition metal series, but no progress has been made in their performance research; the other is the high entropy of single crystal high temperature alloys, mainly Ni-Co based high temperature alloys and Co-Ni based high temperature alloys. A lot of research has been carried out in this direction in terms of organization and performance, and some progress has been made. Although researchers have been trying to develop various alloys that can surpass existing single crystal high temperature alloys and are sufficient for use in high temperature fields in recent years, the actual results are difficult to meet production needs.
[0004] The invention patent with application publication number CN117070825A discloses a single crystal high entropy alloy with excellent high temperature mechanical properties and a preparation method thereof, wherein the chemical composition of the alloy is as follows in atomic percentage: Co 35-40%, Cr 5-7%, Mo 4-6%, Al9-11%, Ta 2-4%, Ti 3-4%, 16%≤Al+Ti+Ta≤17% and the remaining Ni; the preparation method comprises the following steps: placing the raw materials in a crucible of a non-consumable arc melting furnace for repeated melting to obtain a single crystal high entropy alloy master alloy button ingot; placing the single elements in the crucible and stacking them in order from low to high melting points of the alloy elements, and performing electromagnetic stirring during the melting process; cutting the button ingot into metal rods, polishing and ultrasonically cleaning them to obtain a single crystal high entropy alloy master material, using a liquid metal Bridgeman method crystal growth technology to prepare the single crystal high entropy alloy master material into a single crystal alloy, and using a seed crystal method to prepare the single crystal high entropy alloy, wherein the seed crystal used in the seed crystal method has an orientation of <001> During the directional solidification process, the pouring temperature is 1540℃, the holding time is 1h, and the pulling rate is 100μm / s. The single crystal alloy is subjected to solution treatment and aging treatment to obtain a single crystal high entropy alloy. This technical solution focuses on the high temperature mechanical properties of single crystal high entropy alloys, but ignores the room temperature mechanical properties of the alloy.
[0005] At present, in order to address the problems of unbalanced room temperature and high temperature performance of single crystal high entropy alloys, and the inability to achieve both strength and plasticity, the mechanical properties of single crystal high entropy alloys are improved through alloy composition design, heat treatment system optimization, casting process improvement and other means, thereby promoting the high temperature application of single crystal high entropy alloys. Therefore, it is urgent to develop a lightweight and high-strength Ni-Co based single crystal high entropy alloy and its preparation method to meet the demand for balanced room temperature and high temperature performance of single crystal high entropy alloys. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention provides a lightweight and high-strength Ni-Co based single crystal high entropy alloy. The chemical composition of the single crystal high entropy alloy includes eight elements: Ni, Co, Cr, Al, Ti, Mo, W, and Hf. The atomic percentage of each element is Ni 45-55at%, Co 15-20at%, Cr 9-12at%, Al 9-12at%, Ti 4-8at%, Mo 1-2at%, W 0-1at%, Hf0-0.1at%, and the sum of the atomic percentages of each element is 100%.
[0007] Preferably, the mixing entropy ΔS of the single crystal high entropy alloy is mix ≥1.386R, the formula for calculating the mixing entropy is In the formula,
[0008] ΔS mix ——Mixing entropy of single crystal high entropy alloy, J / (mol·K);
[0009] R——gas constant, R=8.314J / (mol·K);
[0010] i——any element among Ni, Co, Cr, Al, Ti, Mo, W, Hf;
[0011] n——the sum of all elements in the single crystal high entropy alloy;
[0012] x i ——Atomic percentage of element i in single crystal high entropy alloy, %.
[0013] In any of the above schemes, preferably, the grain orientation of the single crystal high entropy alloy is <001> The dendrite spacing is 350-430 μm, the loose volume fraction is 0-0.2%, the γ′ structure is composed of a square primary γ′ structure and a granular secondary γ′ structure, the size of the primary γ′ structure is 350-500 nm, the size of the secondary γ′ structure is 10-30 nm, the volume fraction of the primary γ′ structure is 65-70%, the volume fraction of the secondary γ′ structure is 3-7%, and the density of the single crystal high entropy alloy is lower than 8.0 g / cm 3 .
[0014] The present invention also provides a method for preparing a lightweight, high-strength Ni-Co based single crystal high entropy alloy, which is used to prepare any of the above lightweight, high-strength Ni-Co based single crystal high entropy alloys, and comprises the following steps in order:
[0015] Step 1: Use JMatPro, Thermo-Calc or Pandat software to perform thermodynamic calculation simulation according to the composition design ratio of the single crystal high entropy alloy to obtain the liquidus temperature parameters; obtain the eutectic dissolution temperature parameters through DSC melting point test;
[0016] Step 2: weigh out single element Ni, Co, Cr, Al, Ti, Mo, W, and Hf with a purity of more than 99.5% according to the designed composition ratio of the single crystal high entropy alloy for later use;
[0017] Step 3: Put the single element Ni, Co, Cr, Ti, Mo, and W into the crucible of the vacuum induction melting furnace in the designed order, evacuate to a certain vacuum degree, and then heat and melt; when the temperature rises to the refining temperature, add the single element Al and Hf, and perform electromagnetic stirring. After the refining is completed, cast it into a single crystal high entropy alloy master alloy ingot;
[0018] Step 4: Use the high-speed solidification Bridgeman method and seed crystal method to prepare grain orientation <001> The single crystal high entropy alloy test rod is prepared by first placing a single crystal high entropy alloy master alloy ingot into a vacuum melting single crystal directional solidification furnace, evacuating to a certain vacuum degree, and heating for melting; then refining at a certain temperature, and after the refining is completed, lowering the temperature to a pouring temperature; finally, pouring at a certain pulling rate to obtain a cast single crystal high entropy alloy;
[0019] Step 5: placing the cast single crystal high entropy alloy in a heat treatment furnace for solution treatment to obtain a single crystal high entropy alloy in a solid solution state; Step 6: placing the single crystal high entropy alloy in a solid solution state in a heat treatment furnace for primary aging treatment to obtain a single crystal high entropy alloy in a primary aging state;
[0020] Step 7: Place the primary aged single crystal high entropy alloy into a heat treatment furnace for secondary aging treatment to obtain a final heat treated single crystal high entropy alloy, that is, a lightweight and high strength Ni-Co based single crystal high entropy alloy.
[0021] Preferably, in step one, the liquidus temperature parameters include pouring temperature and shell insulation temperature, and the eutectic dissolution temperature parameters include solution treatment temperature, primary aging treatment temperature and secondary aging treatment temperature.
[0022] In any of the above schemes, it is preferred that in step 3, the order of placing the single elements into the crucible from bottom to top is: the first layer is a mixture of 50% Ni and 50% Co, the second layer is a mixture of Mo and W, the third layer is a mixture of Cr and Ti, and the fourth layer is a mixture of 50% Ni and 50% Co; the vacuum degree does not exceed 10 -1 Pa, heating power is 20-50kW, refining temperature is 1500-1600℃, and refining time is 10-30min.
[0023] In any of the above schemes, preferably, in step 4, the vacuum degree does not exceed 10 -2 Pa, heating power is 20-50kW, refining temperature is 1490-1560℃, refining time is 10-20min, pouring temperature is 1470-1540℃, shell insulation temperature is 1450-1520℃, and pulling rate is 2-6mm / min.
[0024] In any of the above schemes, it is preferred that in step five, the process system of the solid solution treatment is as follows: first, argon gas is filled into the heat treatment furnace with a filling pressure of 2-4 bar and a pressure in the furnace of 70-110 Pa, and the heat treatment furnace is heated to 1160-1240°C; then the cast single crystal high entropy alloy is placed in the heat treatment furnace and kept warm for 10-14 hours; finally, the alloy is taken out from the heat treatment furnace and air-cooled.
[0025] In any of the above schemes, it is preferred that in step six, the process system of the primary aging treatment is as follows: first, argon gas is filled into the heat treatment furnace with a filling pressure of 2-4 bar and a pressure in the furnace of 70-110 Pa, and the heat treatment furnace is heated to 1060-1100°C; then, the single crystal high entropy alloy in a solid solution state is placed in the heat treatment furnace and kept warm for 1-5 hours; finally, the alloy is taken out from the heat treatment furnace and air-cooled.
[0026] In any of the above schemes, preferably, in step seven, the process system of the secondary aging treatment is as follows: first, argon is filled into the heat treatment furnace, the filling pressure is 2-4 bar, the pressure in the furnace is 70-110 Pa, and the heat treatment furnace is heated to 840-860°C; then, the single crystal high entropy alloy in the primary aging state is placed in the heat treatment furnace and kept warm for 22-26 hours; finally, the alloy is taken out from the heat treatment furnace and air-cooled.
[0027] The vacuum induction melting furnace, vacuum melting single crystal directional solidification furnace, heat treatment furnace and other equipment used in the present invention can be selected from existing equipment, and no special requirements are made on the model. In the entire preparation process of the single crystal high entropy alloy, the ratio of each element, the placement order of each element in the crucible, the casting process parameters, the shell insulation parameters, the solution treatment system, the primary aging treatment system and the secondary aging treatment system are very critical. Only when the various parameters work together can the expected technical effect of the present invention be achieved.
[0028] The present invention comprehensively considers the influence of various elements on the mechanical properties of room temperature and high temperature alloys when designing the alloy composition, and the specific analysis is as follows:
[0029] Ni: It is a matrix element that provides the FCC structural stability, toughness and ductility of the single crystal high entropy alloy matrix at high temperature. Ni has a low diffusion rate, which supports low-rate thermally activated creep. Ni can also provide Ni elements such as Ni3Al in the γˊ phase.
[0030] Co: It is the second matrix element, which can expand the FCC zone, increase the dissolution temperature and organizational stability of the γˊ phase, reduce the stacking fault energy of the matrix, cause solid solution strengthening, and also reduce the solubility of elements such as Al and Ti in the matrix, thereby increasing the volume fraction of the γˊ phase.
[0031] Cr: It is an antioxidant element. Generally, the higher the Cr content, the better the alloy's heat corrosion resistance and oxidation resistance. Cr can also play a certain solid solution strengthening effect and enhance a certain strength.
[0032] Al: It is a γˊ-forming element, which changes the solubility of each element, increases the reverse bounding energy of γˊ, strengthens the cutting strengthening mechanism, increases the absolute value of the mismatch degree, and causes the coherent strain field around γˊ to be enhanced.
[0033] Ti: It is a γˊ-forming element, which can promote the formation of strengthening precipitates Ni3(Al, Ti) and Ni3Ti, and also affect the mismatch and hardness.
[0034] Mo: It is a solid solution strengthening element that can significantly enhance the lattice constant of the solid solution and enhance the yield strength, increase the long-range elastic stress field, increase the resistance to dislocation movement, and reduce the stacking fault energy.
[0035] W: It is a solid solution strengthening element, which can cause significant expansion of the lattice, prevent dislocation movement, enhance yield strength, and also increase the reverse boundary energy in the alloy, significantly improving the high temperature strength of the alloy.
[0036] Hf: It is a grain boundary strengthening element that can improve medium-temperature strength and plasticity, while providing better fluidity and enhancing the castability of the alloy.
[0037] The lightweight and high-strength Ni-Co based single crystal high entropy alloy and the preparation method thereof of the present invention have the following beneficial effects:
[0038] (1) The present invention takes the influence of density into consideration when designing the composition ratio of the single crystal high entropy alloy. The density of the prepared single crystal high entropy alloy is about 7.7-8.0 g / cm 3 , which is significantly lower than the density of existing single crystal high temperature alloys (about 8.9g / cm 3 ).
[0039] (2) The single crystal high entropy alloy prepared by the present invention has excellent room temperature mechanical properties and high temperature mechanical properties: at room temperature, the tensile strength of the alloy reaches above 1150 MPa, and the elongation reaches above 28%; at 760°C, the tensile strength of the alloy reaches above 1120 MPa, and the elongation reaches above 30%; at 980°C, the tensile strength of the alloy reaches above 650 MPa, and the elongation reaches above 30%; the comprehensive tensile properties reach the standard of the second-generation nickel-based single crystal high-temperature alloy DD6, and have great application potential.
[0040] (3) The single crystal high entropy alloy of the present invention does not contain rare elements such as Re and Ru. Compared with traditional single crystal high temperature alloys, it has advantages in operation and cost, and can effectively carry out engineering applications of the alloy.
[0041] (4) The single crystal high entropy alloy of the present invention does not contain Fe element, but instead contains a small amount of Hf element, which can improve the casting performance of the alloy and avoid a large number of structural defects such as looseness. At the same time, by adding more Cr element and Al element, the oxidation resistance of the alloy is guaranteed. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1A photograph of the dendrite structure of a cast single crystal high entropy alloy in a preferred embodiment of a lightweight and high-strength Ni-Co based single crystal high entropy alloy and a preparation method thereof according to the present invention;
[0043] Figure 2 for Figure 1 Microstructure photograph of the single crystal high entropy alloy in the final heat-treated state in the embodiment shown;
[0044] Figure 3 A photograph of the dendrite structure of a cast single crystal high entropy alloy in another preferred embodiment of the lightweight and high-strength Ni-Co based single crystal high entropy alloy and the preparation method thereof according to the present invention;
[0045] Figure 4 for Figure 3 Microstructure photograph of the single crystal high entropy alloy in the final heat-treated state in the shown embodiment. DETAILED DESCRIPTION
[0046] In order to further understand the content of the present invention, the present invention will be described in detail below in conjunction with specific embodiments.
[0047] Embodiment 1:
[0048] According to a preferred embodiment of the lightweight and high-strength Ni-Co based single crystal high entropy alloy of the present invention, the chemical composition of the single crystal high entropy alloy includes eight elements: Ni, Co, Cr, Al, Ti, Mo, W, and Hf. The atomic percentage of each element is Ni 52at%, Co 18at%, Cr 11at%, Al 11at%, Ti 6at%, Mo 1.5at%, W 0.4at%, and Hf 0.1at%, and the sum of the atomic percentages of each element is 100%.
[0049] The mixing entropy ΔS of the single crystal high entropy alloy mix ≥1.386R, the formula for calculating the mixing entropy is In the formula,
[0050] ΔS mix ——Mixing entropy of single crystal high entropy alloy, J / (mol·K);
[0051] R——gas constant, R=8.314J / (mol·K);
[0052] i——any element among Ni, Co, Cr, Al, Ti, Mo, W, Hf;
[0053] n——the sum of all elements in the single crystal high entropy alloy;
[0054] x i ——Atomic percentage of element i in single crystal high entropy alloy, %.
[0055] The grain orientation of the single crystal high entropy alloy is <001> The dendrite spacing is 378 μm, the loose volume fraction is 0.06%, the γˊstructure consists of a square primary γˊstructure and a granular secondary γˊstructure, the size of the primary γˊstructure is 385 nm, the size of the secondary γˊstructure is 15 nm, the volume fraction of the primary γˊstructure is 67.32%, the volume fraction of the secondary γˊstructure is 3.05%, and the density of the single crystal high entropy alloy is 7.87 g / cm 3 .
[0056] This embodiment also provides a method for preparing a lightweight high-strength Ni-Co based single crystal high entropy alloy, which is used to prepare the above lightweight high-strength Ni-Co based single crystal high entropy alloy, and includes the following steps in order:
[0057] Step 1: Use JMatPro, Thermo-Calc or Pandat software to perform thermodynamic calculation simulation according to the composition design ratio of the single crystal high entropy alloy to obtain the liquidus temperature parameters; obtain the eutectic dissolution temperature parameters through DSC melting point test;
[0058] Step 2: weigh out single element Ni, Co, Cr, Al, Ti, Mo, W, and Hf with a purity of more than 99.5% according to the designed composition ratio of the single crystal high entropy alloy for later use;
[0059] Step 3: Put the single element Ni, Co, Cr, Ti, Mo, and W into the crucible of the vacuum induction melting furnace in the designed order, evacuate to a certain vacuum degree, and then heat and melt; when the temperature rises to the refining temperature, add the single element Al and Hf, and perform electromagnetic stirring. After the refining is completed, cast it into a single crystal high entropy alloy master alloy ingot;
[0060] Step 4: Use the high-speed solidification Bridgeman method and seed crystal method to prepare grain orientation <001> The single crystal high entropy alloy test rod is prepared by first placing a single crystal high entropy alloy master alloy ingot into a vacuum melting single crystal directional solidification furnace, evacuating to a certain vacuum degree, and heating for melting; then refining at a certain temperature, and after the refining is completed, lowering the temperature to a pouring temperature; finally, pouring at a certain pulling rate to obtain a cast single crystal high entropy alloy;
[0061] Step 5: placing the cast single crystal high entropy alloy in a heat treatment furnace for solution treatment to obtain a single crystal high entropy alloy in a solid solution state; Step 6: placing the single crystal high entropy alloy in a solid solution state in a heat treatment furnace for primary aging treatment to obtain a single crystal high entropy alloy in a primary aging state;
[0062] Step 7: Place the primary aged single crystal high entropy alloy into a heat treatment furnace for secondary aging treatment to obtain a final heat treated single crystal high entropy alloy, that is, a lightweight and high strength Ni-Co based single crystal high entropy alloy.
[0063] In step one, the liquidus temperature parameters include pouring temperature and shell insulation temperature, and the eutectic dissolution temperature parameters include solution treatment temperature, primary aging treatment temperature, and secondary aging treatment temperature.
[0064] In step 3, the order of placing the single elements into the crucible from bottom to top is: the first layer is a mixture of 50% Ni and 50% Co, the second layer is a mixture of Mo and W, the third layer is a mixture of Cr and Ti, and the fourth layer is a mixture of 50% Ni and 50% Co; the vacuum degree is 10 -1 Pa, the heating power is 35kW, the refining temperature is 1550℃, and the refining time is 20min.
[0065] In step 4, the vacuum degree is 10 -2 Pa, heating power is 35kW, refining temperature is 1525℃, refining time is 15min, pouring temperature is 1505℃, shell insulation temperature is 1485℃, and pulling rate is 4mm / min.
[0066] In step five, the process system of the solution treatment is as follows: first, argon gas is filled into the heat treatment furnace with a filling pressure of 3 bar and a pressure in the furnace of 90 Pa, and the heat treatment furnace is heated to 1200°C; then the cast single crystal high entropy alloy is placed in the heat treatment furnace and kept warm for 12 hours; finally, the alloy is taken out of the heat treatment furnace and air-cooled.
[0067] In step six, the process system of the primary aging treatment is as follows: first, argon gas is filled into the heat treatment furnace with a filling pressure of 3 bar and a pressure in the furnace of 90 Pa, and the heat treatment furnace is heated to 1080°C; then, the single crystal high entropy alloy in a solid solution state is placed in the heat treatment furnace and kept warm for 3 hours; finally, the alloy is taken out of the heat treatment furnace and air-cooled.
[0068] In step seven, the process system of the secondary aging treatment is as follows: first, argon is filled into the heat treatment furnace with a filling pressure of 3 bar and a pressure in the furnace of 90 Pa, and the heat treatment furnace is heated to 850°C; then, the single crystal high entropy alloy in the primary aging state is placed in the heat treatment furnace and kept warm for 24 hours; finally, the alloy is taken out from the heat treatment furnace and air-cooled.
[0069] In this embodiment, the dendrite structure of the cast single crystal high entropy alloy is as follows: Figure 1 As shown in Figure 2, the microstructure of the final heat-treated single crystal high entropy alloy is as follows: Figure 2 The alloy structure is a γ+γ′ dual-phase structure, the specific structural parameters are shown in Table 1, the specific tensile properties are shown in Table 2, and the specific oxidation resistance is shown in Table 3.
[0070] Table 1 Microstructure parameters of single crystal high entropy alloy
[0071]
[0072] Table 2 Mechanical properties data of single crystal high entropy alloy
[0073] temperature Yield strength(MPa) Tensile strength(MPa) Elongation(%) Sectional shrinkage (%) Room temperature 1001 1167 28.9 24.3 760℃ 964 1131 32.8 44.7 980℃ 485 674 33.1 45.0 DD6-Room temperature 930 970 16.0 19.5 DD6-760℃ 935 1100 8.0 12.0
[0074] Table 3 Oxidation resistance data of single crystal high entropy alloy
[0075] Temperature(℃) <![CDATA[Oxidation rate (g / m 2 ·h)]]> <![CDATA[Scaling loss (g / m 2 )]]> Antioxidant properties 1050 0.011 0.831 Completely antioxidant grade 1100 0.013 3.781 Antioxidant Grade
[0076] The vacuum induction melting furnace, vacuum melting single crystal directional solidification furnace, heat treatment furnace and other equipment used in this embodiment can be selected from existing equipment, and no special requirements are made on the model. In the entire preparation process of the single crystal high entropy alloy, the ratio of each element, the placement order of each element in the crucible, the casting process parameters, the shell insulation parameters, the solution treatment system, the primary aging treatment system and the secondary aging treatment system are all very critical. Only by synergizing the various parameters can the expected technical effect of this embodiment be achieved.
[0077] In designing the alloy composition, the present embodiment comprehensively considers the influence of various elements on the mechanical properties of room temperature and high temperature alloys, and the specific analysis is as follows: (1) Ni is a matrix element, which provides the FCC structural stability, toughness and ductility of the single crystal high entropy alloy matrix at high temperature; Ni has a low diffusion rate, which supports low-rate thermally activated creep; Ni can also provide Ni elements of γˊ phase such as Ni3Al. (2) Co is a second matrix element, which can expand the FCC zone, increase the dissolution temperature and structural stability of the γˊ phase, reduce the stacking fault energy of the matrix, cause solid solution strengthening, and also reduce the solubility of elements such as Al and Ti in the matrix, thereby increasing the volume fraction of the γˊ phase. (3) Cr is an antioxidant element. Generally, the higher the Cr content, the better the heat corrosion resistance and oxidation resistance of the alloy; Cr can also play a certain solid solution strengthening effect and enhance a certain strength. (4) Al is a γˊ forming element, which changes the solubility of each element, increases the reverse boundary energy of γˊ, strengthens the cutting strengthening mechanism, increases the absolute value of the mismatch degree, and causes the coherent strain field around γˊ to be enhanced. (5) Ti is a γˊ-forming element that can promote the formation of strengthening precipitates Ni3(Al, Ti) and Ni3Ti, and also affect the mismatch and hardness. (6) Mo is a solid solution strengthening element that can significantly enhance the lattice constant of the solid solution and enhance the yield strength, increase the long-range elastic stress field, increase the resistance to dislocation movement, and reduce the stacking fault energy. (7) W is a solid solution strengthening element that can cause significant lattice expansion, prevent dislocation movement, enhance yield strength, and also increase the reverse boundary energy in the alloy, significantly improving the high temperature strength of the alloy. (8) Hf is a grain boundary strengthening element that can improve medium temperature strength and plasticity, while providing better fluidity and enhancing the castability of the alloy.
[0078] The lightweight, high-strength Ni-Co-based single crystal high entropy alloy and its preparation method of this embodiment have the following beneficial effects: (1) The influence of density is taken into account when designing the composition ratio of the single crystal high entropy alloy, and the density of the prepared single crystal high entropy alloy is about 7.7-8.0 g / cm 3 , which is significantly lower than the density of existing single crystal high-temperature alloys. (2) The prepared single crystal high-entropy alloy has excellent room temperature mechanical properties and high temperature mechanical properties. The comprehensive tensile properties reach the standard of the second-generation nickel-based single crystal high-temperature alloy DD6, and it has great application potential. (3) Instead of adding Fe element to the single crystal high-entropy alloy, a small amount of Hf element is added, which can improve the casting performance of the alloy and avoid a large number of loose tissue defects. At the same time, by adding more Cr and Al elements, the oxidation resistance of the alloy is guaranteed.
[0079] Embodiment 2:
[0080] According to another preferred embodiment of the lightweight high-strength Ni-Co based single crystal high entropy alloy and preparation method thereof of the present invention, its composition design, process flow, equipment used, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:
[0081] The chemical composition of the single crystal high entropy alloy includes eight elements: Ni, Co, Cr, Al, Ti, Mo, W, and Hf. The atomic percentage of each element is Ni 45at%, Co 20at%, Cr 12at%, Al 12at%, Ti 8at%, Mo 1.9at%, W1at%, and Hf0.1at%, and the sum of the atomic percentages of each element is 100%.
[0082] The grain orientation of the single crystal high entropy alloy is <001> The dendrite spacing is 394 μm, the loose volume fraction is 0.08%, the γ′ structure is composed of a square primary γ′ structure and a granular secondary γ′ structure, the size of the primary γ′ structure is 352 nm, the size of the secondary γ′ structure is 24 nm, the volume fraction of the primary γ′ structure is 68.94%, the volume fraction of the secondary γ′ structure is 6.84%, and the density of the single crystal high entropy alloy is 7.93 g / cm 3 .
[0083] In step one, the liquidus temperature parameters include pouring temperature and shell insulation temperature, and the eutectic dissolution temperature parameters include solution treatment temperature, primary aging treatment temperature, and secondary aging treatment temperature.
[0084] In step 3, the order of placing the single elements into the crucible from bottom to top is: the first layer is a mixture of 50% Ni and 50% Co, the second layer is a mixture of Mo and W, the third layer is a mixture of Cr and Ti, and the fourth layer is a mixture of 50% Ni and 50% Co; the vacuum degree is 10 -1 Pa, the heating power is 20kW, the refining temperature is 1500℃, and the refining time is 10min.
[0085] In step 4, the vacuum degree is 10 -2 Pa, heating power is 20kW, refining temperature is 1490℃, refining time is 10min, pouring temperature is 1470℃, shell insulation temperature is 1450℃, and pulling rate is 2mm / min.
[0086] In step five, the process system of the solution treatment is as follows: first, argon gas is filled into the heat treatment furnace with a filling pressure of 2 bar and a pressure in the furnace of 70 Pa, and the heat treatment furnace is heated to 1160°C; then the cast single crystal high entropy alloy is placed in the heat treatment furnace and kept warm for 10 hours; finally, the alloy is taken out of the heat treatment furnace and air-cooled.
[0087] In step six, the process system of the primary aging treatment is as follows: first, argon gas is filled into the heat treatment furnace with a filling pressure of 2 bar and a pressure in the furnace of 70 Pa, and the heat treatment furnace is heated to 1060°C; then, the single crystal high entropy alloy in a solid solution state is placed in the heat treatment furnace and kept warm for 1 hour; finally, the alloy is taken out of the heat treatment furnace and air-cooled.
[0088] In step seven, the process system of the secondary aging treatment is as follows: first, argon is filled into the heat treatment furnace with a filling pressure of 2 bar and a pressure in the furnace of 70 Pa, and the heat treatment furnace is heated to 840°C; then, the single crystal high entropy alloy in the primary aging state is placed in the heat treatment furnace and kept warm for 22 hours; finally, the alloy is taken out from the heat treatment furnace and air-cooled.
[0089] In this embodiment, the dendrite structure of the cast single crystal high entropy alloy is as follows: Figure 3 As shown in Figure 2, the microstructure of the final heat-treated single crystal high entropy alloy is as follows: Figure 4 The alloy structure is a γ+γ′ dual-phase structure, the specific structural parameters are shown in Table 4, the specific tensile properties are shown in Table 5, and the specific oxidation resistance is shown in Table 6.
[0090] Table 4 Microstructure parameters of single crystal high entropy alloy
[0091]
[0092] Table 5 Mechanical properties data of single crystal high entropy alloy
[0093] temperature Yield strength(MPa) Tensile strength(MPa) Elongation(%) Sectional shrinkage (%) Room temperature 1010 1165 29.1 23.5 760℃ 972 1129 33.1 43.8 980℃ 490 697 33.6 42.1
[0094] Table 6 Oxidation resistance data of single crystal high entropy alloy
[0095] Temperature(℃) <![CDATA[Oxidation rate (g / m 2 ·h)]]> <![CDATA[Scaling loss (g / m 2 )]]> Antioxidant properties 1050 0.010 0.786 Completely antioxidant grade 1100 0.015 4.243 Antioxidant Grade
[0096] Embodiment three:
[0097] According to another preferred embodiment of the lightweight high-strength Ni-Co based single crystal high entropy alloy and preparation method thereof of the present invention, its composition design, process flow, equipment used, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:
[0098] The chemical composition of the single crystal high entropy alloy includes eight elements: Ni, Co, Cr, Al, Ti, Mo, W, and Hf. The atomic percentage of each element is Ni 55at%, Co 18at%, Cr 10at%, Al 10at%, Ti 4at%, Mo 1.9at%, W1at%, and Hf0.1at%, and the sum of the atomic percentages of each element is 100%.
[0099] The grain orientation of the single crystal high entropy alloy is <001> The dendrite spacing is 388 μm, the loose volume fraction is 0.07%, the γ′ structure is composed of a square primary γ′ structure and a granular secondary γ′ structure, the size of the primary γ′ structure is 379 nm, the size of the secondary γ′ structure is 18 nm, the volume fraction of the primary γ′ structure is 69.11%, and the volume fraction of the secondary γ′ structure is 5.21%. The density of the single crystal high entropy alloy is 7.72 g / cm 3 .
[0100] In step one, the liquidus temperature parameters include pouring temperature and shell insulation temperature, and the eutectic dissolution temperature parameters include solution treatment temperature, primary aging treatment temperature, and secondary aging treatment temperature.
[0101] In step 3, the order of placing the single elements into the crucible from bottom to top is: the first layer is a mixture of 50% Ni and 50% Co, the second layer is a mixture of Mo and W, the third layer is a mixture of Cr and Ti, and the fourth layer is a mixture of 50% Ni and 50% Co; the vacuum degree is 10 -1 Pa, the heating power is 50kW, the refining temperature is 1600℃, and the refining time is 30min.
[0102] In step 4, the vacuum degree is 10 -2 Pa, heating power is 50kW, refining temperature is 1560℃, refining time is 20min, pouring temperature is 1540℃, shell insulation temperature is 1520℃, and pulling rate is 6mm / min.
[0103] In step five, the process system of the solution treatment is as follows: first, argon gas is filled into the heat treatment furnace with a filling pressure of 4 bar and a pressure in the furnace of 110 Pa, and the heat treatment furnace is heated to 1240°C; then, the cast single crystal high entropy alloy is placed in the heat treatment furnace and kept warm for 14 hours; finally, the alloy is taken out of the heat treatment furnace and air-cooled.
[0104] In step six, the process system of the primary aging treatment is as follows: first, argon gas is filled into the heat treatment furnace with a filling pressure of 4 bar and a pressure in the furnace of 110 Pa, and the heat treatment furnace is heated to 1100°C; then, the single crystal high entropy alloy in a solid solution state is placed in the heat treatment furnace and kept warm for 5 hours; finally, the alloy is taken out of the heat treatment furnace and air-cooled.
[0105] In step seven, the process system of the secondary aging treatment is as follows: first, argon is filled into the heat treatment furnace, the filling pressure is 4 bar, the pressure in the furnace is 110 Pa, and the heat treatment furnace is heated to 860°C; then, the single crystal high entropy alloy in the primary aging state is placed in the heat treatment furnace and kept warm for 26 hours; finally, the alloy is taken out from the heat treatment furnace and air-cooled.
[0106] In this embodiment, the alloy structure is a γ+γ′ dual-phase structure, the specific structural parameters are shown in Table 7, the specific tensile properties are shown in Table 8, and the specific oxidation resistance is shown in Table 9.
[0107] Table 7 Microstructure parameters of single crystal high entropy alloy
[0108]
[0109] Table 8 Mechanical properties data of single crystal high entropy alloy
[0110] temperature Yield strength(MPa) Tensile strength(MPa) Elongation(%) Sectional shrinkage (%) Room temperature 1002 1158 28.3 24.1 760℃ 969 1127 32.6 44.5 980℃ 508 711 33.8 39.5
[0111] Table 9 Oxidation resistance data of single crystal high entropy alloy
[0112] Temperature(℃) <![CDATA[Oxidation rate (g / m 2 ·h)]]> <![CDATA[Scaling loss (g / m 2 )]]> Antioxidant properties 1050 0.011 0.794 Completely antioxidant grade 1100 0.015 3.992 Antioxidant Grade
[0113] Special note: The technical solution of the present invention involves many parameters, and the synergistic effects between the various parameters need to be comprehensively considered to obtain the beneficial effects and significant progress of the present invention. Moreover, the value ranges of the various parameters in the technical solution are obtained after a large number of experiments. For each parameter and the combination of each parameter, the inventor has recorded a large amount of experimental data. Due to space limitations, the specific experimental data will not be disclosed here.
[0114] It is not difficult for those skilled in the art to understand that the lightweight, high-strength Ni-Co-based single crystal high-entropy alloy and its preparation method of the present invention include any combination of the invention content and specific implementation methods of the above-mentioned invention specification and the various parts shown in the drawings. Due to the limited space and to make the specification concise, the various schemes composed of these combinations are not described one by one. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lightweight, high-strength Ni-Co based single crystal high entropy alloy, characterized in that: The chemical composition of the single crystal high entropy alloy includes eight elements: Ni, Co, Cr, Al, Ti, Mo, W, and Hf. The atomic percentage of each element is Ni 45-55at%, Co 15-20at%, Cr 9-12at%, Al 9-12at%, Ti 4-8at%, Mo 1-2at%, W 0-1at%, and Hf0-0.1at%, and the sum of the atomic percentages of each element is 100%.
2. The lightweight and high-strength Ni-Co based single crystal high entropy alloy according to claim 1, characterized in that: The mixing entropy ΔS of the single crystal high entropy alloy mix ≥1.386R, the formula for calculating the mixing entropy is In the formula, ΔS mix ——Mixing entropy of single crystal high entropy alloy, J / (mol·K); R——gas constant, R=8.314J / (mol·K); i——any element among Ni, Co, Cr, Al, Ti, Mo, W, Hf; n——the sum of all elements in the single crystal high entropy alloy; x i ——Atomic percentage of element i in single crystal high entropy alloy, %.
3. The lightweight and high-strength Ni-Co based single crystal high entropy alloy according to claim 2, characterized in that: The grain orientation of the single crystal high entropy alloy is <001> The dendrite spacing is 350-430 μm, the loose volume fraction is 0-0.2%, the γ′ structure is composed of a square primary γ′ structure and a granular secondary γ′ structure, the size of the primary γ′ structure is 350-500 nm, the size of the secondary γ′ structure is 10-30 nm, the volume fraction of the primary γ′ structure is 65-70%, the volume fraction of the secondary γ′ structure is 3-7%, and the density of the single crystal high entropy alloy is lower than 8.0 g / cm 3 .
4. A method for preparing a lightweight and high-strength Ni-Co based single crystal high entropy alloy, characterized in that: The method for preparing the lightweight, high-strength Ni-Co based single crystal high entropy alloy according to any one of claims 1 to 3 comprises the following steps in chronological order: Step 1: Use JMatPro, Thermo-Calc or Pandat software to perform thermodynamic calculation simulation according to the composition design ratio of the single crystal high entropy alloy to obtain the liquidus temperature parameters; obtain the eutectic dissolution temperature parameters through DSC melting point test; Step 2: weigh out single element Ni, Co, Cr, Al, Ti, Mo, W, and Hf with a purity of more than 99.5% according to the designed composition ratio of the single crystal high entropy alloy for later use; Step 3: Put the single element Ni, Co, Cr, Ti, Mo, and W into the crucible of the vacuum induction melting furnace in the designed order, evacuate to a certain vacuum degree, and then heat and melt; when the temperature rises to the refining temperature, add the single element Al and Hf, and perform electromagnetic stirring. After the refining is completed, cast it into a single crystal high entropy alloy master alloy ingot; Step 4: Use the high-speed solidification Bridgeman method and seed crystal method to prepare grain orientation <001> The single crystal high entropy alloy test rod is prepared by first placing a single crystal high entropy alloy master alloy ingot into a vacuum melting single crystal directional solidification furnace, evacuating to a certain vacuum degree, and heating for melting; then refining at a certain temperature, and after the refining is completed, lowering the temperature to a pouring temperature; finally, pouring at a certain pulling rate to obtain a cast single crystal high entropy alloy; Step 5: placing the cast single crystal high entropy alloy into a heat treatment furnace for solution treatment to obtain a single crystal high entropy alloy in a solid solution state; Step 6: placing the single crystal high entropy alloy in a solid solution state into a heat treatment furnace for primary aging treatment to obtain a single crystal high entropy alloy in a primary aging state; Step 7: Place the primary aged single crystal high entropy alloy into a heat treatment furnace for secondary aging treatment to obtain a final heat treated single crystal high entropy alloy, that is, a lightweight and high strength Ni-Co based single crystal high entropy alloy.
5. The method for preparing a lightweight and high-strength Ni-Co based single crystal high entropy alloy according to claim 4, characterized in that: In step one, the liquidus temperature parameters include pouring temperature and shell insulation temperature, and the eutectic dissolution temperature parameters include solution treatment temperature, primary aging treatment temperature, and secondary aging treatment temperature.
6. The method for preparing a lightweight and high-strength Ni-Co based single crystal high entropy alloy according to claim 5, characterized in that: In step 3, the order of placing the single elements into the crucible from bottom to top is: the first layer is a mixture of 50% Ni and 50% Co, the second layer is a mixture of Mo and W, the third layer is a mixture of Cr and Ti, and the fourth layer is a mixture of 50% Ni and 50% Co; the vacuum degree does not exceed 10 -1 Pa, heating power is 20-50kW, refining temperature is 1500-1600℃, and refining time is 10-30min.
7. The method for preparing a lightweight and high-strength Ni-Co based single crystal high entropy alloy according to claim 6, characterized in that: In step 4, the vacuum degree does not exceed 10 -2 Pa, heating power is 20-50kW, refining temperature is 1490-1560℃, refining time is 10-20min, pouring temperature is 1470-1540℃, shell insulation temperature is 1450-1520℃, and pulling rate is 2-6mm / min.
8. The method for preparing a lightweight and high-strength Ni-Co based single crystal high entropy alloy according to claim 7, characterized in that: In step five, the process system of the solution treatment is as follows: first, argon is filled into the heat treatment furnace, the filling pressure is 2-4 bar, the pressure in the furnace is 70-110 Pa, and the heat treatment furnace is heated to 1160-1240°C; then the cast single crystal high entropy alloy is placed in the heat treatment furnace and kept warm for 10-14 hours; finally, the alloy is taken out of the heat treatment furnace and air-cooled.
9. The method for preparing a lightweight and high-strength Ni-Co based single crystal high entropy alloy according to claim 8, characterized in that: In step six, the process system of the primary aging treatment is as follows: first, argon is filled into the heat treatment furnace, the filling pressure is 2-4 bar, the pressure in the furnace is 70-110 Pa, and the heat treatment furnace is heated to 1060-1100°C; then the single crystal high entropy alloy in the solid solution state is placed in the heat treatment furnace and kept warm for 1-5 hours; finally, the alloy is taken out from the heat treatment furnace and air-cooled.
10. The method for preparing a lightweight and high-strength Ni-Co based single crystal high entropy alloy according to claim 9, characterized in that: In step seven, the process system of the secondary aging treatment is as follows: first, argon is filled into the heat treatment furnace, the filling pressure is 2-4 bar, the pressure in the furnace is 70-110 Pa, and the heat treatment furnace is heated to 840-860°C; then the single crystal high entropy alloy in the primary aging state is placed in the heat treatment furnace and kept warm for 22-26 hours; finally, the alloy is taken out from the heat treatment furnace and air-cooled.
Citation Information
Patent Citations
Ingredients of nickel-based single crystal superalloy and application of nickel base single crystal superalloy
CN107130140A
High-temperature-resistant high-entropy alloy with high room-temperature plasticity and preparation method thereof
CN114150205A
Rare earth hybrid nickel-based high-temperature alloy with high oxygen content, preparation method and application
CN114622113A
Radiation-resistant nickel-based alloy
CN116732389A
Precipitated phase dispersion-strengthened hydrogen embrittlement-resistant nickel-based single crystal high-temperature alloy and preparation method thereof
CN117512404A
Cited By
Smelting method of digital high-carbon nickel-based wear-resistant high-temperature alloy
CN117926065A